Organized crime and development : challenges and policy options in West Africa's fragile states - Vorrath, Judith (2015)
Zusammenfassung: The development implications of transnational organized crime (TOC) have attracted growing attention in Germany and at the international level in recent years. Fragile and conflict-affected countries, which are generally regarded as especially vulnerable to TOC and its impacts, are a particular focus of interest. In the development policy debate, it has long been recognized that TOC and criminal violence are among the reasons why most fragile states have not achieved the Millennium Development Goals (MDGs). For this reason, too, the development community has no option but to deal with the issue of organized crime and the risks that it poses to fragile states. Organized crime is a cross-cutting issue, not merely a security problem. Indeed, the development community is already dealing with TOC or TOC-relevant sectors more often than is generally assumed - whether in bilateral programmes to promote alternative development in drug cultivation areas or when supporting the establishment of sustainable fishing and forestry sectors in partner countries. The analysis of illicit economies in Liberia, Sierra Leone and Guinea shows that the threats posed by TOC change over time and that their impacts vary across sectors. In conditions of fragile statehood, TOC can act as an external stressor, an economy of violence, a form of state capture, and/or a world of existence/survival. The corresponding threats can be systematically analyzed in order to identify entry points and trade-offs in the development community's engagement with TOC. (SWP Research Paper)